﻿The direct and indirect effects of damming on the Hippopotamus amphibius population abundance and distribution at Bui National Park, Ghana - Godfred Bempah; Martin Kobby Grant; Changhu Lu; Amaël Borzée (Nature Conservation, 2022)
Landscape changes resulting from human activities have resulted in range restrictions and substantial reductions in population sizes of most animals. The construction of hydroelectric dams has the same effect on species, but the study of their impact on semi-aquatic megafauna species is limited. We examined the response of a Hippopotamus amphibius population to the inundation of their habitat after the construction of a hydroelectric dam in Bui National Park, Ghana. We conducted an abundance and distribution survey of H. amphibius and compared the population size from our results with a pre-dam construction survey to determine changes in the abundance and distribution of the species within the focal area. Furthermore, we conducted a landscape analysis to estimate land cover before and after the dam construction and determined if the changes in land cover were related to the changes in population of H. amphibius. Finally, we conducted selected interviews to understand additional threats to the species perceived by the local population, as indirect effects of the dam construction. Contrary to our original hypothesis on an increase in the abundance of H. amphibius in the medium term (within a decade) through population recovery after the disturbances caused by the construction of the dam, we found lower numbers of H. amphibius after the dam construction, compared to the pre-dam results. The results indicated a reduced abundance from 209 H. amphibius individuals in 2003 to 64 H. amphibius individuals in 2021. Some individuals may have migrated to areas outside the reserve during damming when their habitat was disturbed. The amount of land covered by water increased from 0.41% before damming to 19.01% after damming, which flooded the resting and grazing sites of the H. amphibius. We conclude that the abundance and distribution of H. amphibius significantly and negatively decreased after the construction of the dam at the Bui National Park. We tentatively relate this decrease to the species’ semi aquatic ecology and sensitivity to changes in both the terrestrial and aquatic environment. The activities of human settlement encroachment such as poaching, as well as associated land cover changes, affected the stability of the H. amphibius population. However, as the species can survive in the medium to long term when effective management plans are implemented, we recommend H. amphibius to be given high conservation priorities by enhancing strict laws for habitat protection.